2019
DOI: 10.1590/0102-311x00208517
|View full text |Cite
|
Sign up to set email alerts
|

Association between sociodemographic characteristics and sexual behaviors among a nationally representative sample of adolescent students in Brazil

Abstract: Although low socioeconomic status (SES) adolescents suffer from higher rates of adverse sexual and reproductive health outcomes, evidence on the association between SES and sexual behaviors has been less consistent. A cross-sectional analysis of the association between sociodemographic characteristics (household wealth, maternal education and race/ethnicity) and sexual behaviors (sexual initiation, multiple sexual partners, inconsistent condom use and inconsistent contraceptive use) of Brazilian adolescents wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 30 publications
2
15
0
7
Order By: Relevance
“…The higher frequency of sexual risk behavior in males agrees with the literature that points to this association regardless of how RSB is evaluated, as well as when examining the components of RSB separately (lower condom use and greater number of partners) 1,8,11 . Being male implies being subjected to a repertoire of social pressures, such as encouraging the expression of sexuality in the name of "masculinity," manhood proof and heterosexuality, resulting in the increase in the number of partners 1,22 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The higher frequency of sexual risk behavior in males agrees with the literature that points to this association regardless of how RSB is evaluated, as well as when examining the components of RSB separately (lower condom use and greater number of partners) 1,8,11 . Being male implies being subjected to a repertoire of social pressures, such as encouraging the expression of sexuality in the name of "masculinity," manhood proof and heterosexuality, resulting in the increase in the number of partners 1,22 .…”
Section: Discussionsupporting
confidence: 84%
“…In Brazil, the evaluation of a representative sample of high school students indicated that 32% of the students did not use condoms in sexual intercourses that occurred in the month before the survey 8 . Among undergraduate students, non-use of condom in the last sexual intercourse ranged from 85.7% to 38.6% 2,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Most studies worldwide to date that have evaluated the associated factors of condom non-use of adolescents have focused on demographics [10,11]; substance use (alcohol, tobacco, and prohibited substances) [10,12]; and sexual activity factors (number of sexual partners, age of sexual debut) [7,13]. Most of these studies, however, have also used local or non-representative samples [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In a survey with the general population, 36% of participants between the ages of 15 and 24 had not used condoms in their last sexual intercourse (MS, 2016). Woolley and Macinko (2019) report a similar proportion in the sample of the National Survey of School Health (PeNSE 2015;n = 120,301), with 33% of girls and 30% of boys stating that they had not used a condom in their last intercourse. It is important to consider that different recall period may generate different results.…”
Section: Seção: Artigomentioning
confidence: 91%
“…Currently, STI cases are increasing in the young population of Brazil, including adolescents over the age of 13 (MS 2018a;2018b;Saffier et al, 2017). However, even with widespread communication of the importance of preventive behavior and the increased accessibility of condoms in health services in Brazil, reports of condom use are still low (MS, 2016;Woolley & Macinko, 2019). In a survey with the general population, 36% of participants between the ages of 15 and 24 had not used condoms in their last sexual intercourse (MS, 2016).…”
Section: Seção: Artigomentioning
confidence: 99%